blaKPC and Efflux Pump Genes in Klebsiella pneumoniae Isolated from Surgical Site Infections - Maharjan, Renuka; Poudel, Prativa; Dewasy, Bijoylakshmi; Tuladhar, Reshma; Aryal, Manita; Singh, Praveer Raj; Pokharel, Hanoon; Singh, Shantikumar; Singh, Anjana (Anti-Infective Agents, 2026)
IntroductionSurgical site infections (SSIs) are the most common surgery related complication in healthcare worldwide. Infections due to carbapenem resistant Klebsiella pneumoniae are increasing dramatically with significant impact on surgical patients.ObjectiveThe aim of this study was to detect blaKPC and efflux pump genes in K. pneumoniae isolated from infected surgical wounds.MethodsA study including 291 patients was conducted at Birat Medical College Teaching Hospital (BMCTH), Biratnagar, from October 2021 to October 2022. Specimens were collected from the patients with SSIs under aseptic conditions and sent to the microbiology laboratory. K. pneumoniae was identified by VITEK 2. The presence of carbapenemase was phenotypically screened by the modified carbapenem inactivation method (mCIM). blaKPC and efflux pump genes were detected by polymerase chain reaction (PCR).Results and DiscussionA total of 134 (46%) specimens were culture positive, out of which 24 (30%) were identified as K. pneumoniae with 11 (45.8%) isolates resistant to carbapenem. Tigecycline and colistin were the most effective drugs against K. pneumoniae. Among these isolates, seven were found to be mCIM positive. blaKPC was absent in all mCIM-positive isolates, however, efflux pump genes (acrA and acrB) were detected in all of the carbapenem-resistant isolates.ConclusionA high prevalence of carbapenem-resistant K. pneumoniae could be attributed to the efflux pump genes. This finding suggests that the AcrAB efflux pump may be the major virulence factor that can contribute to multidrug-resistant strains.
Keywords: polymerase chain reaction